A molecular survey, whole genome sequencing and phylogenetic analysis of astroviruses from roe deer - Jamnikar-Ciglenecki, Urska (BMC Vet Res, 2020)
BACKGROUND: Although astroviruses (AstV) have been detected in a variety of host species, there are only limited records of their occurrence in deer. One of the most important game species in Europe, due to its meat and antlers, is roe deer. Infected game animals can pose a threat to the health of other animals and of humans, so more attention needs to be focused on understanding the diversity of viruses in wildlife. The complete genome and organization of the roe deer AstV genome have not so far been described. RESULTS: In our study, 111 game animals were screened for the presence of AstV. While no AstVs were detected in red deer, wild boar, chamois and mouflon, AstV RNA was present in three samples of roe deer. They were further subjected to whole genome sequencing with next generation sequencing. In this study, two AstV genomes were assembled; one in sample D5–14 and one in sample D12–14, while, in sample D45–14, no AstV sequences were identified. The complete coding sequences of the AstV SLO/D5–14 strain genome and of the almost complete genome of the AstV SLO/D12–14 strain were determined. They showed a typical Mamastrovirus organization. Phylogenetic analyses and amino acid pairwise distance analysis revealed that Slovenian roe deer AstV strains are closely related to each other and, also, related to other deer, bovine, water buffalo, yak, Sichuan takin, dromedary, porcine and porcupine AstV strains - thus forming a highly supported group of currently unassigned sequences. CONCLUSIONS: Our findings suggest the existence of a new Mamastrovirus genogroup might be constituted while this aforementioned group is distantly related to Mamastrovirus genogroups I and II. In this study, additional data supporting a novel taxonomic classification are presented.